Orta hat asimetrileri ve tedavi seçenekleri - Serpil Çokakoğlu; Ruhi Nalçacı (Cumhuriyet University, 2012)
Nowadays the importance given to facial aesthetic is increasing. The coincidence of facial, maxiller and mandibuler dental midlines is very important requiring facial aesthetic. Midline asymmetries can be seen in form of  dental, skeletal and/or soft tissue asymmetries. In most of cases midline asymmetries accompany with facial asymmetries. Even if the amount of patients with midline asymmetry is not known to be aware of their problems, dental midline deviations observing without facial deformity can be noticed by most of patients with the help of their orthodontists. Symmetry of the dental and facial midlines comes at the beginning of the factors affecting treatment planning. For this reason midlines and due to the multifactorial etiology of asymmetries all of the factors that cause asymmetry must be evaluated properly during treatment planning. In this present article, our aim is try to give answers following questions: "Which factors cause midline asymmetries?'', "Which type of asymmetries can be seen commonly in clinical?'', "Do the using mechanics affect occlusion?'',"Is it necessary to correct each type of midline asymmetries?'', "Is there any mean threshold for esthetically acceptable midline asymmetries? Keywords: Midline, asymmetry.   ÖZET Günümüzde yüz estetiğine verilen önem giderek artmaktadır. Fasiyal, maksiller ve mandibular dental orta hatların uyumu yüz estetiğinin sağlanması açısından oldukça önemlidir. Orta hat asimetrileri dental, iskeletsel ve/veya yumuşak dokuyu ilgilendiren şekilde görülebilir. Birçok olguda fasiyal asimetri şeklinde karşımıza çıkar. Asimetrili hastaların probleminin farkında olup olmadığı bilinmese de, fasiyal deformitenin gözlenmediği dental orta hat sapmaları çoğu hasta tarafından ancak ortodontistin yönlendirmesiyle fark edilebilir. Dental ve fasiyal orta hatların uyumu tedavi planlanmasını etkileyen faktörlerin başında gelir. Bu nedenle tedavi planlaması esnasında orta hatlar mutlaka değerlendirilmeli, multifaktöriyel etyolojisi nedeniyle asimetriye neden olan etkenler doğru bir şekilde belirlenmelidir. Bu derlemede amacımız; " Orta hat asimetrilerine neden olan faktörler nelerdir?", "Klinikte hangi tip orta hat asimetrileri ile karşılaşabiliriz?", "Kullanılan mekanikler okluzyonu etkiler mi ?", "Her orta hat asimetrisi tedavi gerektirir mi?" , "Orta hat asimetrilerinin estetik açıdan kabul edilebilir sınır bir değeri var mı?" gibi sorulara yanıt bulmaktır.